the question is below-

Asked by  | 21st Aug, 2008, 02:38: PM

Expert Answer:

we are given that ap:cp = 1:2  and bq:cq= 1:2

in triangle acq , aq2 = ac2+ cq2  but cq= 2/3 bc

replacing cq in above expression

aq2 = ac2+ (2/3 bc)2   => 9aq2 = 9ac2+ 4bc2

similarly in triangle bcp , bp2 = bc2+cp2   , here also cp = 2/3 ac

replacing it we get 9bp2 = 9bc2+4ac2

Answered by  | 12th Sep, 2008, 04:42: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.